Implementasi Model Pembelajaran Modeling Partisipan Pada Mata Pelajaran Akidah Akhlak di MA Balongrejo Sumobito Jombang - Widiasari, Tri; Munif, Achmad Abdul (LP3M STIT Al Urwatul Wutsqo Jombang, 2023)
This study aims to describe the Participant Modeling Learning Model in the Subject of Akhlak Aqidah at MA Balongrejo Sumobito. This study uses a qualitative research method with a case study type of research. Data Collection Techniques using Interviews, Observations, and documentation. This method was used by researchers to obtain data related to Participant Modeling Strategies in the Subject of Aqidah Akhlak at MA Balongrejo Sumobito Jombang. Data analysis techniqueData Reduction (Data reduction) Data Display (Data Presentation) Conclusion Drawing/Verification. Data Validity Test is carried out by: Participation Extension, Observation Persistence and Triangulation. The result of the research is that the Participant Modeling learning model planning consists of 4 steps, namely: 1). Preparing material, 2). Choosing a model, 3. Guided participation. The application of the Participant Modeling Learning Model in the Akidah Akhlak Subject at MA Balongrejo Sumobito has three stages, namely: 1). Model preparation, 2). Model demonstration, 3). Observation of students, 4). Teacher explanation. Evaluation of Participant Modeling Learning Models There are three things that must be evaluated by students, namely: 1). Learning process, 2). Learning outcomes, 3. Learning program.